Comparative Review of Personal Data Protection Policy in Indonesia and The European Union General Data Protection Regulation - Valentina Ancillia Simbolon; Vishnu Juwono (Publik : (Jurnal Ilmu Administrasi), 2022)
Data leakage is one of the high potentials for criminal acts in cyberspace. The Indonesian government passed the Personal Data Protection Act (UU PDP) to ensure the security of every citizen's personal data. This study aims to compare the policies of the Personal Data Protection Act with the European Union General Data Protection Regulations (EU-GDPR). This study uses a qualitative descriptive analysis method with data from previous studies and official releases from the Indonesian government and the European Union. The results of this study illustrate that the PDP Law and the EU-GDPR have the same arrangements regarding the rights of personal data subjects. In the data processing aspect, the principle of processing personal data in the PDP Law is not mandatory. In contrast, in the EU-GDPR, the principle of processing personal data is mandatory. In the aspect of controlling and processing personal data, both rights and responsibilities are almost the same, both for the PDP Law and the EU-GDPR. In the aspect of imposing sanctions, EU-GDPR is more apparent in the mechanism of imposing sanctions in the form of fines. While in the PDP Law, sanctions consist of administrative sanctions, criminal sanctions, and criminal fines, the mechanism of imposing sanctions is not yet clear.